Study of The Performance of The Gas Turbine Power Plants From The Simple To Complex Cycle: A Technical Review - Ibrahim, Thamir K.; Mohammed, Mohammed Kamil; Al Doori, Wadhah Hussein Abdulrazzaq; Al-Sammarraie, Ahmed Tawfeeq; F., Basrawi (Akademia Baru Publishing (M) Sdn Bhd, 2019)
In this study, a comprehensive review of previous studies on GT power plants was conducted. The recent decades have witnessed several studies on the modelling and simulation of GT performance. This review concentrated on a simple cycle GT power plant (GTPP) with a 2-shaft, regenerative, reheat, intercooler, complex cycle GT with effect intercooler, regenerative and reheat. Further reviews focused on the influence of operating conditions on the performance of GTPP with more emphasis on the complex and simple cycles of the GT. Finally, the technical review focused on the improvement of the performance of the GTPP. However, information can be found on the assessment of the performance of GTPPs, especially, for GTPP operation in both ambient conditions and complex configurations. This review adopted a systematic approach to ensure that this study can be conducted properly to contribute to the existing information in this field.